2019
DOI: 10.1097/inf.0000000000002446
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Antiretroviral Therapy in Adolescents With Vertical HIV Infection Leads to Different Cytokine Profiles Depending on Viremia Persistence

Abstract: Background: We investigated immune activation, exhaustion markers and cytokine expression upon stimulation in adolescents with vertical HIV infection. Methods: Thirty adolescents receiving antiretroviral therapy (ART) for vertical HIV infection, including 12 with detectable viral load (HIV/DET), 18 with undetectable viral load (HIV/UND) and 30 control adolescents without HIV infection (CONTROL), were evaluated for immune activation and programmed cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
9
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
4
9
2
Order By: Relevance
“…Our results suggest that immune activation persists in YWVH, even among those on ART and virologically suppressed. These results contrast with previous results suggesting that treated and suppressed patients had a T‐cell activation and immune exhaustion profile similar to uninfected adolescents [ 31 ]. Distinct mention deserves results obtained for CD69 on T cells, considered the earliest activation marker during infections and increased levels have been associated with increased viral load [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results suggest that immune activation persists in YWVH, even among those on ART and virologically suppressed. These results contrast with previous results suggesting that treated and suppressed patients had a T‐cell activation and immune exhaustion profile similar to uninfected adolescents [ 31 ]. Distinct mention deserves results obtained for CD69 on T cells, considered the earliest activation marker during infections and increased levels have been associated with increased viral load [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, our study that was cited by Shen et al [1] showed that adolescents with detectable viral load had significantly lower IL-6 levels than controls, and those with an undetectable viral load had IL-6 levels comparable with controls [3].…”
contrasting
confidence: 84%
“…By contrast, evidence of immune exhaustion can be more readily observed in in-vitro T-cell stimulation experiments as some level of immune exhaustion is enough to interfere with the response to the intense stimulus applied in those assays. That is what we have performed in our study, so that adolescents with detectable viral load were the ones with the lowest cytokine levels [3]. The same approach was described by Underwood et al [5].…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Figure2(A) The correlation between IFN-γ (n=40) and CD4 cells in HIV infected patients, with normal response to retroviral therapy, with CD4 decreasing rates less than 35 cell/microliter/year, or viral load lower than 20 copies/milliliter. (B) The correlation between sMICA (n=19) and CD4 cells in HIV infected patients with normal response to retroviral therapy, with CD4 decreasing rates less than 35 cell/microliter/year or viral load lower than 20 copies/milliliter [2][3][4][5][6][7][8]. …”
mentioning
confidence: 99%